Una politica industriale e tecnologica per l’Italia - Lucchese, Matteo; Nascia, Leopoldo; Pianta, Mario (Argomenti, 2016)
The crisis started in 2008 has accelerated the decline of Italy’s industry. An analysis of the current tools used in Italy’s industrial and innovation policy shows that they are not able to support a revival of production and investment in Italy and to reduce Italy’s gap in technological activities. A strong recovery depends on the development of a more ambitious industrial policy plan, combining Italian and European initiatives.